On the Origins of Administrative and Judicial Discretion in Russian Administrative and Jurisdictional Activities - S. V. Schepalov (Сибирское юридическое обозрение, 2023)
The article continues the discussion organized by the journal with the participation of professors Yuri P. Solovey and Petr P. Serkov on the problem of administrative discretion. The Author proposes to look at the difference between the internal content of administrative discretion and judicial discretion, which is evolutionarily incorporated in the proceedings on administrative offenses. The reader is invited to the conclusion that administrative responsibility has historically been imposed by government bodies for disobedience to the current management order. The authorized body acts on behalf of the public authority, and the responsibility imposed by it means the responsibility of a person to the government for disobedience to its internal policy. In Russia, it arose in the 1920s, when V. I. Lenin considered the people's courts weak in resolving issues of the application of public law penalties to persons who do not comply with the norms established by the Soviet government. The judicial order arose and evolved as a people's revision of the public authorities' initiative for administrative prosecution. Such a reform of administrative responsibility was carried out after the death of I.V. Stalin N. S. Khrushchev, who, trying to restore the lost trust of society in the authorities, believed that administratively punishable acts should cause condemnation not only of the authorities, but also of society. Some categories of cases of administrative offenses were assigned to the competence of the people's court. The court acts on behalf not of the public authority, but of the country as a whole. When imposing a punishment, the court declares the person guilty before the country not of an anti-government, but of an anti-social act. Administrative responsibility is evolutionarily connected with the discretion of the jurisdictional body. Its content is various social rules and values, including principles, as well as political considerations. Administrative discretion is dominated by managerial values: general prevention, ensuring public order, controllability of the masses, tax collection, implementation of state policy, etc. Judicial discretion, being realized on behalf of the country, reproduces the social norms and values of Russian society as a whole. Both legislative norms and managerial values are preserved, but become part of the general range of social norms and values, which is dominated by the universal principles of justice, reasonableness, proportionality and an adequate balance of private and public interests.